Penerapan Kriptografi untuk Pengamanan Data Nilai Siswa dengan Algoritma Super Enkripsi - Jefry G G Saragih (ADA Journal of Information System Research, 2025)
This study discusses the application of cryptography using the super-encryption method as a solution for securing student grade data at SMA Negeri 5 Medan, which still relies on manual systems and is therefore vulnerable to manipulation and data leakage. Super-encryption was chosen because it combines two cipher techniques to strengthen security, with the Vigenere Cipher algorithm employed as one of the methods for both encryption and decryption processes. The research stages include literature review, system requirements analysis, architecture and algorithm design, application implementation, testing, and result documentation. The encryption process successfully transformed the plaintext of student grades into ciphertext that is difficult for unauthorized parties to interpret, while the decryption process accurately restored the ciphertext to its original form using the same key. The testing results indicate that this method ensures the confidentiality and integrity of academic data while enhancing the security of multi-user information systems. Thus, this research emphasizes that implementing super-encryption in student grade management systems not only protects privacy and data authenticity but also serves as a strategic solution to address cybersecurity threats in the field of education.